2015
DOI: 10.1016/j.jmaa.2015.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Operator space and operator system analogs of Kirchberg's nuclear embedding theorem

Abstract: The Gurarij operator space NG introduced by Oikhberg is the unique separable 1-exact operator space that is approximately injective in the category of 1-exact operator spaces and completely isometric linear maps. We prove that a separable operator space X is nuclear if and only if there exist a linear complete isometry ϕ : X → NG and a completely contractive projection from NG onto the range of ϕ. This can be seen as the operator space analog of Kirchberg's nuclear embedding theorem. With similar methods we al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Theorem 3.3 implies that a separable exact operator space is nuclear if and only if it is completely isometric to the range of a completely contractive projection of NG. This recover a result from [80]. The existence of the universal operator on NG described in It is clear that when Z, X are Banach spaces endowed with the canonical minimal operator space structure, then P : Z → X is a complete facial quotient if and only if it is a facial quotient.…”
Section: More Examplessupporting
confidence: 66%
“…Theorem 3.3 implies that a separable exact operator space is nuclear if and only if it is completely isometric to the range of a completely contractive projection of NG. This recover a result from [80]. The existence of the universal operator on NG described in It is clear that when Z, X are Banach spaces endowed with the canonical minimal operator space structure, then P : Z → X is a complete facial quotient if and only if it is a facial quotient.…”
Section: More Examplessupporting
confidence: 66%
“…The operator spaces G q . The following amalgamation result is proved in [23,Lemma 3.1]; see also [25, Lemma 2.1]. Lemma 3.1.…”
Section: 2mentioning
confidence: 97%
“…Precise uniqueness of the Gurarij operator space was later proven in [23] by realizing the Gurarij operator space (henceforth referred to as NG) as the Fraïssé limit of the class of finite-dimensional 1-exact operator spaces. In [24], the second author established the existence and uniqueness of the Guarij operator system GS, which is the Fraïsé limit Goldbring's work was partially supported by NSF CAREER grant DMS-1349399.…”
Section: Introductionmentioning
confidence: 99%
“…The function systems approach has been adopted in the work of Conley and Törnquist [13] and, independently, in [45,46], where it is shown that the class of finite-dimensional function systems is a Fraïssé class. Its limit can be identified with the function system A(P) corresponding to the Poulsen simplex, which we will call the Poulsen system.…”
Section: 1mentioning
confidence: 99%